'Broken-heart' syndrome: ventricular septal perforation in a takotsubo cardiomyopathy. (May 2016) - Pepe, Martino; Paradies, Valeria; Bortone, Alessandro; De Cillis, Emanuela; Cafaro, Alessandro; Acquaviva, Tommaso; Masi, Filippo; Quagliara, Donato; Favale, Stefano
Takotsubo cardiomyopathy (TTC) is a form of acute left ventricular dysfunction usually reversible and with favorable prognosis. Ventricular septal perforation (VSP) is a very rare life-threatening complication. Percutaneous closure of VSP, despite being challenging, is a possible alternative to surgical repair. We present the first case of an 84-year-old patient with a TTC-related VSP treated by percutaneous approach. The case highlights the need of reconsidering the worldwide accepted consideration of TTC as benignant and allows some speculations on the optimal management of VSP in terms of timing, patient selection and possible alternative interventions.